Performance of lettuce submitted to the rock dust remineralizer and doses of efficient microorganisms - Sousa, Westefann dos Santos [UNESP]; Campos, Thiago Souza [UNESP]; Vaz Souza, Ane Gabriele [UNESP]; Nascimento Cintra, Pedro Henrique; Faria, Layanara Oliveira; Borges dos Santos, Talles Eduardo (Univ Estadual Mato Grosso Sul, 2021)
The use of soil remineralizers with efficient microorganisms (EM) can represent an effective and sustainable alternative to improve the growth, development, and yield of cultivated plants. Thus, the present study aimed to evaluate the effect of different doses of EM, in the presence or absence of rock dust (RD), on the development of iceberg lettuce, cultivar Lucy Brown. The design used was completely randomized, arranged in a 2 x 5 factorial scheme, with four replications. The treatments consisted of the presence and absence of RD in the substrate composition, combined with five commercial product doses based on EM (0, 2, 4, 6, and 8 L ha(-1)). At 30 days after transplanting, root and stem length, head circumference, the number of leaves, stem diameter, leaf area, fresh matter of root, stem, leaf, and shoot, and dry matter of root, stem, leaf, and shoot were evaluated. There was an interaction between the factors for most variables of economic importance. The dose of 4.5 L ha(-1) of the product based on EM, combined with PR, implied the best performance of iceberg lettuce under the studied cultivation conditions.
Keywords: Natural phosphate; Lactuca sativa; Beneficial microorganisms; Vegetable nutrition